Persea americana Peel: A Promising Source of Nutraceutical for the Mitigation of Cardiovascular Risk in Arthritic Rats Through the Gut–Joint Axis - Doha A. Mohamed; Asmaa A. Ramadan; Hoda B. Mabrok; Gamil E. Ibrahim; Shaimaa E. Mohammed (Biomolecules)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by the inflammation of synovial fluid. The incidence of cardiovascular diseases (CVDs) is increasing in RA patients. This research is the first report to investigate the anti-arthritic effect of avocado peel nutraceutical (APN) and its potential in mitigating the cardiovascular risk associated with RA. The antioxidant activity and phytochemical composition of APN were assessed. The potential interaction of APN’s active compounds with protein tyrosine phosphatase non-receptor type 22 (PTPN22) was studied using molecular docking. The impact of APN on the plasma lipid profile, oxidative and inflammatory markers, and the indices of coronary risk and atherogenicity as CVD markers were evaluated. The gene expression of COX-2, IL-6, IL-1β, IL-10, and TNF-α in liver and spleen tissues were measured. The rat gut microbiota profile was investigated using 16S rRNA amplicon sequencing. APN exhibited high antioxidant activity, low atherogenicity and thrombogenicity indices, and a high ratio of hypocholesterolemic to hypercholesterolemic fatty acids indicating its cardioprotective potential. The administration of APN led to a reduction in oxidative stress markers, inflammatory markers, dyslipidemia, and CVD markers. APN administration downregulated the expression of COX-2, IL-6, IL-1β, and TNF-α genes, while the IL-10 gene was significantly upregulated in the liver and spleen. Treatment with APN was favorable in restoring eubiosis in the gut by modulating RA-associated bacterial taxa linked to impaired immune function and cardiometabolic diseases. In molecular docking, β-amyrin and ellagic acid showed the highest binding affinity for PTPN22. APN may represent a promising approach to ameliorating the cardiovascular risk of RA. The present results will be offering a foundation for future in-depth research in nutraceuticals from agriculture by-products. Additionally, they will be supporting the public health policies aimed at preventing and controlling rheumatoid arthritis.